(3GdSQ GdecJhe aj WdSeGJ GdchGcHs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3Ce agPG cJGH JLeY ajg edNU eG hUd EdjfG ef Yde GdWdSeGJ hGdSMQjGJ hGdYRGFe hOYhI GdchGcH s
(3BNQgG (B:s
(3aEf GdTGH ZPG cGf gcPG Ke TQY ai Cf jJYde GdMceI CbHdf Cf dGjchf ajdSha RhQ hdG Mcje HgQL hdG HGWd habfG Gddg hEjGce CjgG GdENhGf GdeNdUhf Cf JchfhG gcPG Ef TGA Gddg Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3HChdgG agQSJ ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B989s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs